The squirrel on the train - Hearne, Kevin (Oberon's meaty mysteries, 2017)
Oberon the Irish wolfhound is off to Portland to smell all the things with canine companions wolfhound Orlaith and Boston terrier Starbuck, and, of course, his human, ancient Druid Atticus O'Sullivan. The first complication is an unmistakable sign of sinister agendas afoot: a squirrel atop the train. But an even more ominous situation is in store when the trio plus Atticus stumble across a murder upon arrival at the station. They recognize Detective Gabriela Ibarra, who's there to investigate. But they also recognize the body--or rather that the body is a doppelganger for Atticus himself. The police, hampered by human senses of smell and a decided lack of canine intuition, obviously can't handle this alone. Not with Atticus likely in danger. Oberon knows it's time to investigate once more---for justice! For gravy! And possibly greasy tacos! Alongside his faithful Druid, Oberon and the other loyal hounds navigate by nose through Portland to find a bear-shifter friend with intel, delicious clues at the victim's home, and more squirrels. Always more squirrels! But will our hungry band of heroes be able to identify the culprit before someone else is murdered? Will there be mystery meat in gravy as a reward or tragedy in store for the world's (or at least the Pacific Northwest's) greatest dog detective? -- Provided by publisher.